Hysteresis-free and fast response polymer-stabilised blue phase liquid crystals. Issue 5 (8th April 2020) - Li, Xuan; Sun, Dong-Peng; Hou, De-Shan; Zhu, Ji-Liang; He, Zheng-Hong; Li, Jian; Han, Wen-Ming
ABSTRACT: The electro-optical properties of γ -Fe2 O3 nanoparticles doped polymer-stabilized blue phase liquid crystals are investigated. The experimental results show that the hysteresis were effectively suppressed by doping γ -Fe2 O3 . When doped with γ -Fe2 O3 of 1.0 wt. %, hysteresis-free and fast response were achieved by the coupling effect of polymer and nanoparticle. Our research provides excellent guidance for the development of electro-optical devices with high grey scale accuracy and fast response. Graphical abstract: